Comparative quantitative study on national identity in contemporary social psychology - Fabrykant M.S. (Современная зарубежная психология, 2018)
The article presents a review of quantitative comparative cross-cultural studies on national identity conducted by psychologists during the last two decades. It considers the relation of theoretical and methodological grounds of these studies with the general agenda of the contemporary social psychology, interdisciplinary studies on nations and nationalism, and empirical resources of cross-national surveys. The relevant publications demonstrate the prevalence of descriptive approach in psychological studies, while sociology and political science mostly use the explanatory research approach on factors affecting the national identity. Nevertheless, the explanatory research results reveal the underestimated cross-cultural variability of correlations between national identity components and the correspondence of these components to essentially different cognitive mechanisms. To fulfil the potential of their discipline, cross-cultural psychologists studying national identity should explore relations of national identity with basic values and attitudes with paying a special attention to cross-level interaction effects and social dynamics.